Open Mexico network in the implementation of national open data policy - Valenzuela Mendoza, Rafael Enrique (IGI Global, 2018)
The objective of the chapter is to identify some barriers to accessing public data through the study of one of the pillars of Mexico’s national open data policy, the Open Mexico Network. Based on the exploratory analysis of the “Mexico Abierto network” and the description of a case study in northern Mexico, an attempt is made to answer the following question: Does Mexico’s national open data policy generate timely data and have efficient access to data? and the final question, Is it easy for citizens to obtain? The study identifies major problems from the design of the national policy of open data, such as not having foreseen the creation of positive incentives for local governments to update the databases in the “México Abierto network.”